2000
DOI: 10.1128/mcb.20.6.1923-1930.2000
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl Coenzyme A Stimulates RNA Polymerase II Transcription and Promoter Binding by Transcription Factor IID in the Absence of Histones

Abstract: Protein acetylation has emerged as a means of controlling levels of mRNA synthesis in eukaryotic cells. Here we report that acetyl coenzyme A (acetyl-CoA) stimulates RNA polymerase II transcription in vitro in the absence of histones. The effect of acetyl-CoA on basal and activated transcription was studied in a human RNA polymerase II transcription system reconstituted from recombinant and highly purified transcription factors. Both basal and activated transcription were stimulated by the addition of acetyl-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
(37 reference statements)
2
34
0
Order By: Relevance
“…30 -32), the ACTR transcriptional coactivator (33), and the basal transcription factors TFIIE and TFIIF (34) have been observed. Moreover, it has been found that acetyl-CoA can enhance the transcription of naked DNA (greater than 5-fold) as well as the binding of TFIID to promoter DNA in the absence of histones (35). (Note that we observe a more modest 1.2-2.5-fold increase in transcription by acetyl-CoA with naked DNA templates (Fig.…”
Section: Fig 3 Transcriptional Activators Function Effectively Withmentioning
confidence: 74%
“…30 -32), the ACTR transcriptional coactivator (33), and the basal transcription factors TFIIE and TFIIF (34) have been observed. Moreover, it has been found that acetyl-CoA can enhance the transcription of naked DNA (greater than 5-fold) as well as the binding of TFIID to promoter DNA in the absence of histones (35). (Note that we observe a more modest 1.2-2.5-fold increase in transcription by acetyl-CoA with naked DNA templates (Fig.…”
Section: Fig 3 Transcriptional Activators Function Effectively Withmentioning
confidence: 74%
“…One study, designed to address a link between protein acetylation and RNA polymerase II transcription in a histone-free system, found that addition of acetyl-CoA stimulated the DNA-binding activity of TFIID. However, they determined that it did so not through direct acetylation of TFIID or TFIIA, but through a different mechanism (Galasinski et al, 2000). Other studies have addressed the question of histone acetylation and TBP binding.…”
Section: Discussionmentioning
confidence: 99%
“…We are also examining the effect of the addition of small molecule effectors such as acetyl CoA (11,88), other GTFs such as TFIIA and TFIIB (Refs. 28 and 30, and data not shown), the putative TAF130p accessory factor Bdf1p (89), and trans-activators upon the kinetic and equilibrium binding interactions of these molecules using the same spectroscopic and biochemical assays.…”
Section: Discussionmentioning
confidence: 99%